BLIGHTSIM: A new potato late blight model simulating the response of Phytophthora infestans to diurnal temperature and humidity fluctuations in relation to climate change - Narouei-Khandan, H.A.; Shakya, S.; Garrett, K.A.; Goss, E.M.; Dufault, N.S.; Andrade-Piedra, J.L.; Asseng, Senthold; Wallach, Daniel; Bruggen, A.H.C. van (MDPI, 2020)
Temperature response curves under diurnal oscillating temperatures differ from those under constant conditions for all stages of the Phytophthora infestans infection cycle on potatoes. We developed a mechanistic model (BLIGHTSIM) with an hourly time step to simulate late blight under fluctuating environmental conditions and predict late blight epidemics in potato fields. BLIGHTSIM is a modified susceptible (S), latent (L), infectious (I) and removed (R) compartmental model with hourly temperature and relative humidity as driving variables. The model was calibrated with growth chamber data covering one infection cycle and validated with field data from Ecuador. The model provided a good fit to all data sets evaluated. There was a significant interaction between average temperature and amplitude in their effects on the area under the disease progress curve (AUDPC) as predicted from growth chamber data on a single infection cycle. BLIGHTSIM can be incorporated in a potato growth model to study effects of diurnal temperature range on late blight impact under climate change scenarios.